Heat-Induced Changes in the Physical Properties of a New Premixed Calcium Silicate-Containing Root Canal Sealer: An In Vitro Study - Ryota Ito; Satoshi Watanabe; Akira Kouno; Shinya Yamauchi; Takashi Okiji (MDPI AG, 2024)
This study aimed to examine how heating affects the physical properties of a newly developed premixed calcium silicate-containing sealer (AH Plus Bioceramic Sealer; AHB), in comparison with EndoSequence BC Sealer (ES), AH Plus Jet (AH), and Pulp Canal Sealer. The setting time, flow, and film thickness were tested with or without heating at 100 °C for 30 or 60 s, in accordance with ISO6876:2012 standards. Ultrastructural and elemental analyses were performed with scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). Data were analyzed using one-way analysis of variance (ANOVA) with a Tukey post hoc test (α = 0.05). All sealers exhibited significantly shorter setting time and flow after heating at 100 °C for 30 and 60 s (p < 0.05). After heating, AHB showed a significantly higher film thickness compared to that of the other materials (p < 0.05). None of the tested properties of heat-applied AHB and ES met ISO standards, except the setting time in ES. The SEM/EDS results for AHB and ES were not affected by heating. The detected changes in physical properties can negatively impact the performance of premixed calcium silicate-containing sealers, particularly AHB, when warm vertical compaction is employed.